(NsTIHOTWORENIQ(B: [1825-1836] /s (N~ASTX (B2s - (NpU[KIN(B, (NaLEKSANDR sERGEEWI^s ((NmOSKWA(B:s (NhUDOVESTWENNAQ LITERATURA(B,s, 1974)
(Nw TOM WO[LI STIHOTWORENIQ a(B.(Ns(B. (NpU[KINA(B, (NNAPISANNYE W (B1825-1836 (NGG(B.s
rus
Keywords: (NsTIHOTWORENIQs